1997
DOI: 10.4102/jsava.v68i4.892
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high broiler litter diets as survival ration on the health of sheep

Abstract: The use of broiler litter as an emergency feed during droughts and other periods of feed shortages was evaluated in terms of its effect on the health of sheep. Pure broiler litter (i.e. excreta plus wood shavings), and litter mixed with 7.5 or 15 % molasses were fed for 83 days to 2-year-old wethers. The addition of molasses to the litter caused a significant increase (p < 0.01) in feed intake and final body mass. Various parameters such as plasma enzyme activity, plasma metabolite concentrations and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The increase in voluntary DM intake observed with increasing additions of molasses to the broiler litter is in agreement with the findings of a previous study (Mavimbela et al, 1997). Silanikove et al (1987) observed a high intake of litter by beef cows and concluded that the small particle size of broiler litter resulted in fast escape from the rumen and a relatively high intake.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The increase in voluntary DM intake observed with increasing additions of molasses to the broiler litter is in agreement with the findings of a previous study (Mavimbela et al, 1997). Silanikove et al (1987) observed a high intake of litter by beef cows and concluded that the small particle size of broiler litter resulted in fast escape from the rumen and a relatively high intake.…”
Section: Discussionsupporting
confidence: 81%
“…This results in a higher water concentration in the faeces, compared to faeces from digesta moving slowly through the colon. In a previous study (Mavimbela et al, 1997), lambs gained more weight when broiler litter plus 15% molasses was fed than at lower inclusion levels of molasses. This was suggested to be due mainly to the higher DM intake of the molasses supplemented group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations